Review: Manfaat Feromon Sek Pada Ordo Lepidoptera Untuk Pengendalian Hama Lepidoptera - Syariful Banun (Universitas Lambung Mangkurat, 2021)
Lepidoptera is one of the orders of the phylum Arthropoda Insecta class consist of butterflies that are active during the day and moths at night. Both of them belong to the order Lepidoptera and have an important role in the ecosystem. Beneficial role for plants as pollinating insects and Â disadvantaged role as pests of cultivated plants. An example is the fall armyworm Spodoptera sp attacking rice plants, Pteroma sp attacks sengon plants, and Helicoverpa armigera attacks red chili plants. One of the efforts to control pests is the use of sex pheromones. Several types of sex pheromones were identified, for example the sex pheromone of the cabbage leaf caterpillar Pluttela xylostella was )-11-hexadecenal, (Z)-11-hexadecenol, and (Z)-11-hexadecenyl acetate with ratio 8:18:100 and 10:1:90. Potato tuber borer (Phthorimaea operculella Zell.) sex pheromones is (E,Z)- 4,7-13 Ac (trans-4, cis-7-tridecadienyl acetate) and (E,Z,Z)-4,7,10-13 Ac (trans-4, cis-7, cis-10-tridecatrienyl acetate) with ratio 1 : 2,5. Using pheromones sex on agricultural land can significantly suppress Lepidoptera pest populations.